Decision Making for Selection in Science Project Learning Management Model Using the Analytical Hierarchy Process: A Case Study Anukoolnaree School - Autthalak, Mallika; Lawong, Amin (Journal of Engineering and Industrial Technology, Kalasin University, 2023)
The purpose of this research is to select learning management models for science projects by considering mixed teaching method factors. There are five factors, group process, thinking training, The troubleshooting process, emphasizes puzzle-based teaching and collaborative teaching and four alternatives for science projects to make it suitable for the learner. At the Secondary 5, the science subject group applied the decision-making process by means of an Analytical Hierarchy Process (AHP) case study at Anukoolnaree School. The results showed that teachers in the science subject group decided on an experimental science project with the highest sum of factors in each of their choices. It has an overall score of 49.66, and the most important factor in deciding on a learning management model using science projects is cognitive exercise. The score is 51.85 percent.